Gubernur Jenderal VOC Jan Pieterszoon Coen dan Pembangun Kota Batavia (1619-1629) - Rani Noviyanti (Universitas Indraprasta PGRI, 2017)
ABSTRACTThe establishment of the city of Batavia on the west coast of the north coast of Java, cannot be separated from the role of a figure named Jean Pieterzoon Coen. Although previously Jayakarta (the name before Batavia), was controlled and built by Pangeran Fatahillah, the situation and conditions in the social and economic fields of Jayakarta were not like the management of J.P. Coen. After Jayakarta was controlled by the VOC, through a military expedition policy designed by JP. Coen, the condition of the city of Jayakarta slowly gradually increased in the social and economic fields. The increase in the city of Batavia in the social and economic fields was based on three JP policies. Coen was quite brave, namely increasing trade activities in the Sunda port of Kalapa, revitalizing the position of the islands in northern Batavia as a base of administration and defense and security, and opening the widest door for Chinese traders and immigrants. The three policies, in fact, were purely based on the thoughts outlined by JP. Coen, after taking over the Jayakarta area from the mastery of Prince Fatahillah.Keywords: J.P. Coen, Kota Batavia.ABSTRAKPendirian kota Batavia di sebelah barat pesisir pantai utara Jawa, tidak dapat dipisahkan dari peran seorang tokoh yang bernama Jean Pieterzoon Coen. Meskipun sebelumnya Jayakarta (nama sebelum Batavia), dikuasai dan dibangun oleh Pangeran Fatahillah, akan tetapi situasi dan kondisi dalam bidang sosial dan ekonomi Jayakarta tidak seperti pada masa pengelolaan J.P. Coen. Setelah Jayakarta dikuasai oleh VOC, melalui kebijakan ekspedisi militer yang dirancang oleh JP. Coen, keadaan kota Jayakarta perlahan demi perlahan semakin meningkat dalam bidang sosial dan ekonomi. Peningkatan kota Batavia dalam lapangan sosial dan ekonomi dilatari oleh tiga kebijakan JP. Coen yang cukup berani, yakni meningkatkan aktivitas perdagangan di pelabuhan Sunda Kalapa, merevitalisasi kedudukan pulau-pulau di utara Batavia sebagai basis adiministrasi dan pertahanan dan keamanan, serta membuka pintu seluas-luasnya bagi pedagang dan pendatang etnis Tionghoa. Tiga kebijakan tersebut, sejatinya meurpakan murni hasil pemikiran yang dituangkan olh JP. Coen, setelah mengambil alih wilayah Jayakarta dari penguasaan pangeran Fatahillah.Kata Kunci : J.P. Coen, Kota Batavia.